Computed Tomography With Intravenous Contrast Alone: The Role of Intra‐abdominal Fat on the Ability to Visualize the Normal Appendix in Children. (15th August 2013) - Garcia, Madelyn; Taylor, George; Babcock, Lynn; Dillman, Jonathan R.; Iqbal, Vaseem; Quijano, Carla V.; Wootton‐Gorges, Sandra L.; Adelgais, Kathleen; Anupindi, Sudha A.; Sonavane, Sushil; Joshi, Aparna; Veeramani, Murugusundaram; et al.
Abstract Background Computed tomography (CT) with enteric contrast is frequently used to evaluate children with suspected appendicitis. The use of CT with intravenous (IV) contrast alone (CT IV) may be sufficient, however, particularly in patients with adequate intra‐abdominal fat (IAF). Objectives The authors aimed 1) to determine the ability of radiologists to visualize the normal (nondiseased) appendix with CT IV in children and to assess whether IAF adequacy affects this ability and 2) to assess the association between IAF adequacy and patient characteristics. Methods This was a retrospective 16‐center study using a preexisting database of abdominal CT scans. Children 3 to 18 years who had CT IV scan and measured weights and for whom appendectomy history was known from medical record review were included. The sample was chosen based on age to yield a sample with and without adequate IAF. Radiologists at each center reread their site's CT IV scans to assess appendix visualization and IAF adequacy. IAF was categorized as "adequate" if there was any amount of fat completely surrounding the cecum and "inadequate" if otherwise. Results A total of 280 patients were included, with mean age of 10.6 years (range = 3.1 to 17.9 years). All 280 had no history of prior appendectomy; therefore, each patient had a presumed normal appendix. A total of 102 patients (36.4%) had adequate IAF. The proportion of normal appendices visualized with CT IV was 72.9% (95% confidence interval [CI] = 67.2% to 78.0%); the proportions were 89% (95% CI = 81.5% to 94.5%) and 63% (95% CI = 56.0% to 70.6%) in those with and without adequate IAF (95% CI for difference of proportions = 16% to 36%). Greater weight and older age were strongly associated with IAF adequacy (p < 0.001), with weight appearing to be a stronger predictor, particularly in females. Although statistically associated, there was noted overlap in the weights and ages of those with and without adequate IAF. Conclusions Protocols using CT with IV contrast alone to visualize the appendix can reasonably include weight, age, or both as considerations for determining when this approach is appropriate. However, although IAF will more frequently be adequate in older, heavier patients, highly accurate prediction of IAF adequacy appears challenging solely based on age and weight.